Answer :

SinA can be expressed in terms of sec A as:

sinA = √sin^{2}A

sin A = √(1 -cos^{2}A)

Now,

cos A can be expressed in terms of secA as:

cosA =

tanA can be expressed in the form of sec A as:

As, 1 + tan^{2}A = sec^{2}A

⇒ tan A =± √(sec^{2}A -1)

As A is acute angle,

And tan A is positive when A is acute,

So,

tan A = √(sec^{2}A -1)

cosec A can be expressed in the form of sec A as:

cosec A =

cot A can be expressed in terms of sec A as:

cot A =

as, 1 + tan^{2}A = sec^{2}A

=

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Trigonometric Identities39 mins

Trigonometric Identities-II43 mins

Heights and Distances-I45 mins

Introduction to Linear Equations in Two Variables62 mins

Area Related to Circles- Important Formula and Concepts59 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation